2014
DOI: 10.1177/1043659614523994
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Mammography Use Among Older American Indian and Alaska Native Women

Abstract: American Indian and Alaska Native (AIAN) women have relatively high breast-cancer mortality rates despite the availability of free or low-cost screening. Purpose This qualitative study explored issues that influence the participation of older AIAN women in mammography screening through tribally directed National Breast and Cervical Cancer Early Detection Programs (NBCCEDP). Methods We interviewed staff (n=12) representing five tribal NBCCEDP and conducted four focus groups with AIAN women ages 50 to 80 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…Among AIs, a study on perceived barriers to breast cancer screening were identified in a study of 255 AI women in Oklahoma, which found that barriers (i.e., long wait-times and complex referral processes) predicted the receipt of mammography in the past two years (Tolma, Stoner, Li, Kim, &Engelman, 2014). Perceived vulnerability to breast cancer, access to quality health care, affordable screenings, and the cultural appropriateness of health care providers were all factors that affected older AI women’s mammography use (James, Gold, St John-BlackBird, & Brown Trinidad, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Among AIs, a study on perceived barriers to breast cancer screening were identified in a study of 255 AI women in Oklahoma, which found that barriers (i.e., long wait-times and complex referral processes) predicted the receipt of mammography in the past two years (Tolma, Stoner, Li, Kim, &Engelman, 2014). Perceived vulnerability to breast cancer, access to quality health care, affordable screenings, and the cultural appropriateness of health care providers were all factors that affected older AI women’s mammography use (James, Gold, St John-BlackBird, & Brown Trinidad, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Research among non-Navajo women highlights similar communication problems including silence, avoidance, or mutual protection around cancer (Kenen, Arden-Jones, & Eeles, 2004;Zhang & Siminoff, 2003). Other barriers to cancer communication in families include fear, distress, and the perceived stigma of cancer (Burhansstipanov, Dignan, Wound, Tenney, & Vigil, 2000;Guadagnolo et al, 2009;Hodge et al, 2000;James, Gold, St John-BlackBird, & Brown Trinidad, 2015;Kenen et al, 2004;Zhang & Siminoff, 2003). Thus, efforts toward cancer prevention and control have been compromised primarily due a lack of collectivistic approaches (i.e., including the family or community) and an inability to communicate cancer information accurately and meaningfully to those who need it.…”
mentioning
confidence: 99%
“…Experience and satisfaction with breast cancer screening was discussed by Ndikum-Moffor, Braiuca, Daley, Gajewski, & Engelman (2013) following their nine focus groups of AI/ AN women. Seven themes emerged including three that were similar to findings from Daley, Kraemer-Diaz, et al (2012) and James et al (2015). The themes identified were knowledge, communication and awareness, barriers, and motivation.…”
Section: Qualitative Studiesmentioning
confidence: 69%
“…Perceptions and experiences with breast cancer screening were described by 33 AI/AN women who participated in four focus groups and by 12 staff who were interviewed over the phone (James et al, 2015). The researchers used the PRECEDE-PROCEED framework when identifying two sets of semistructured interview questions to be used, one for the women and one for the staff.…”
Section: Qualitative Studiesmentioning
confidence: 99%